Nickel-based single-crystal high-temperature alloy brazing repair material and method
By using nickel-based single-crystal high-temperature alloy brazing repair materials and vacuum heating technology, the problem of difficulty in repairing large-sized cracks in the existing technology is solved, and efficient repair of nickel-based single-crystal high-temperature alloy parts is achieved, and the performance of the repaired parts is improved.
Patent Information
- Application Number
- CN202311103333.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-29
AI Technical Summary
The existing brazing repair process is difficult to effectively repair large-size cracks, resulting in high maintenance costs and short service life of nickel-based single-crystal high-temperature alloy parts.
A nickel-based single crystal high temperature alloy brazing repair material is used, which includes a uniformly mixed brazing powder and a base material powder with the same components as the nickel-based single crystal high temperature alloy to be repaired, and brazing is repaired by vacuum heating.
Effective brazing repair of large-sized cracks is achieved, and the weld structure formed is free of holes, inclusions or crack defects, and has good high-temperature mechanical properties and high-temperature durability.
Smart Images

Figure CN119525817A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of welding, and in particular relates to a nickel-based single crystal high-temperature alloy brazing repair material and a repair method. Background Art
[0002] Nickel-based single crystal high-temperature alloys have good corrosion resistance and mechanical properties under high-temperature service conditions due to the elimination of grain boundaries, especially good high-temperature creep properties. Therefore, nickel-based single crystal alloys are widely used in the hot end components of current aircraft engines, such as high-pressure turbine blades or guide blades. During long-term service, turbine blades are periodically subjected to impact and corrosion, and it is inevitable that ablation, cracks, wear and other damage will occur. Brazing repair of damaged nickel-based single crystal high-temperature alloy parts is an important issue in the repair and maintenance of aircraft engines. Existing brazing repair processes mostly use the capillary phenomenon formed by narrow cracks to promote the uniform flow of molten brazing material in the gap. Once the crack gap has developed to a larger size and the capillary phenomenon disappears, it is difficult to repair the damaged parts by brazing, which increases the maintenance cost of nickel-based single crystal alloy parts and limits the service life of nickel-based single crystal alloy parts. Summary of the invention
[0003] The purpose of the present invention is to provide a nickel-based single crystal high temperature alloy brazing repair material, which can effectively perform brazing repair on large-size cracks. The present invention also provides a nickel-based single crystal high temperature alloy brazing repair method.
[0004] According to an embodiment of one aspect of the present invention, a nickel-based single crystal high-temperature alloy brazing repair material is provided, which includes a first brazing filler metal, wherein the first brazing filler metal includes a uniformly mixed brazing powder and a base material powder having the same composition as the nickel-based single crystal high-temperature alloy to be repaired; wherein the brazing powder includes the following components by weight: 8%-18% Cr, 3%-12% Co, 1%-6% W, 1%-6% Ta, 2%-6% Al, 1%-5% B, no more than 4% Mo, no more than 5% Hf, no more than 3% Re, and the remainder is Ni and unavoidable impurities; the weight ratio of the brazing powder in the first brazing filler metal is 5% to 50%.
[0005] In the brazing repair material, Cr, Co, W, and Mo elements can be dissolved in the weld matrix after brazing, thereby improving the weld strength and the high-temperature oxidation resistance and corrosion resistance of the weld. The Al element can participate in the formation of the γ' phase, thereby improving the weld strength and oxidation resistance. The Ta element and the Re element can improve the stability of the γ' phase, thereby increasing the use temperature of the weld joint; however, when Ta is excessive, it will precipitate in the form of a compound and is difficult to eliminate in the subsequent treatment process, which has an adverse effect on the weld strength. The B element can reduce the melting point of the brazing filler metal and improve the wettability of the brazing filler metal melt. The Hf element can reduce the melting point of the brazing filler metal and improve the strength and plasticity of the weld structure. The C element and the Si element are prone to form harmful precipitates in the weld area, so they need to be controlled as impurity elements so that their content does not exceed the upper limit of the solid solubility of C and Si in the alloy matrix, so that the structure after brazing repair has better mechanical properties. Furthermore, mixing brazing powder and base material powder in the first brazing filler metal can improve the wettability of the first brazing filler metal and the weld, improve the structural uniformity of brazing repair of large-sized cracks, and improve the strength of the repaired parts.
[0006] Furthermore, in some embodiments, the weight ratio of the brazing powder in the first brazing filler metal is 10%-40%. The parent material component has a higher melting point than the brazing powder, and controlling the specific gravity of the parent material powder can improve the high temperature mechanical properties of the weld structure. The parent material does not melt during the welding process and serves as a skeleton for the parent material of the connected parts during the weld repair process.
[0007] Furthermore, in some embodiments, the particle size of the brazing powder and the parent material powder does not exceed 110 μm. Smaller particle size is beneficial to accelerate the melting of the brazing material during the brazing process and improve the uniformity of the welding structure.
[0008] Furthermore, in some embodiments, the brazing powder and the parent material powder are spherical or nearly spherical particles. The spherical or nearly spherical parent material powder can be prepared by vacuum gas atomization and the like, can be fully mixed, and can be quickly melted during the brazing process.
[0009] Furthermore, in some embodiments, the brazing repair material further includes a second brazing material, which is the brazing powder and is applied to the surface of the first brazing material. The second brazing material composed of low melting point brazing powder is applied to the surface of the first brazing material, and the second brazing material region first melts and forms a liquid phase during the brazing process, thereby improving the uniformity of the liquid phase distribution in the weld and avoiding defects such as pores and gaps in the weld structure after solidification.
[0010] Furthermore, in some embodiments, the nickel-based single crystal high-temperature alloy is DD4, DD6 or CMSX-4 alloy.
[0011] According to another embodiment of the present invention, a nickel-based single crystal high-temperature alloy brazing repair method is provided, which adopts the nickel-based single crystal high-temperature alloy brazing repair material in any of the above embodiments, and includes the following steps: providing a part to be repaired with a crack, filling the first brazing material in the crack; coating the brazing powder on the surface of the first brazing material filled in the crack until the first brazing material is completely covered; vacuum heating the part to be repaired, the heating temperature is 1150℃-1230℃, the holding time is 20min-180min, and the brazing repair is completed. Using this method, the weld structure formed in the brazing repair process is fully welded, without holes, inclusions or crack defects, and has good high-temperature mechanical properties and high-temperature durability.
[0012] Furthermore, in some embodiments, the maximum width of the crack of the part to be repaired is not less than 0.25 mm. The method can effectively repair cracks with a maximum width of not less than 0.25 mm.
[0013] Furthermore, in some embodiments, the first solder filled in the crack is flush with the surface of the part to be repaired.
[0014] Furthermore, in some embodiments, the parts repaired by brazing are subjected to high-temperature tensile testing at 1000° C., and the strength is not less than 60% of the parent material. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is an electron microscope photograph of the brazing powder in one embodiment;
[0016] Figure 2 This is an electron microscope photograph of a mixture of brazing powder and base material powder in one embodiment;
[0017] Figure 3 Schematic diagram of solder arrangement position in one embodiment.
[0018] Figure 4 A metallographic structure photograph of a weld in one embodiment;
[0019] Figure 5 A metallographic structure photograph of a weld in another embodiment;
[0020] Figure 6 A metallographic structure photograph of a weld in another embodiment;
[0021] Figure 7 A pair of proportional metallographic photos of the weld.
[0022] The purpose of the above drawings is to explain the present invention in detail so that those skilled in the art can understand the technical concept of the present invention, but it is not intended to limit the present invention. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.
[0024] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The phrase appearing in various locations in the specification does not necessarily refer to the same embodiment, nor is it limited to mutually exclusive independent or alternative embodiments. Those skilled in the art should be able to understand that the embodiments herein may be combined with other embodiments without causing structural conflicts.
[0025] In the description of this article, the terms "first", "second" and the like are only used to distinguish different objects, and cannot be understood as indicating relative importance or limiting the quantity, specific order or primary and secondary relationship of the described technical features. In the description of this article, the meaning of "plurality" is at least two.
[0026] An embodiment of one aspect of the present invention provides a nickel-based single crystal high-temperature alloy brazing repair material to achieve brazing repair of nickel-based single crystal high-temperature alloy parts with large gap cracks.
[0027] In one embodiment, two DD6 alloy samples are used to simulate the nickel-based single crystal high-temperature alloy parts to be repaired. The brazing alloy is prepared according to the following ratio: by weight, 9.6% Cr, 10.7% Co, 1.5% W, 4.3% Ta, 3.7% Al, 2.5% B, and the balance is Ni and unavoidable impurities. The brazing alloy is treated by vacuum gas atomization to prepare a brazing powder with a particle size of ≤110μm, and its scanning electron microscope photo is as shown in FIG. Figure 1 As shown; the DD6 base alloy was treated by vacuum gas atomization to obtain base powder with a particle size of ≤110μm. Part of the brazing powder and the base powder were evenly mixed in a weight ratio of 1:4. The morphology of the mixed powder under the scanning electron microscope is shown in Figure 2 As shown in the figure, both the brazing powder and the base material powder are spherical or nearly spherical fine particles.
[0028] The solder powder is mixed with a binder to obtain a paste-like second solder; the mixed powder of the solder powder and the base material powder is mixed with a binder to obtain a paste-like first solder. In different embodiments, the binder can be an organic binder such as polystyrene or polymethyl methacrylate that can be completely vaporized at high temperature.
[0029] The surfaces of the two DD6 alloy samples were polished and cleaned with alcohol to remove the oil on the surface to determine the surface composite cleanliness requirements of the samples. The gap between the two DD6 alloy samples was controlled by a fixture to maintain a gap of about 0.3mm to simulate the state of a part with a large-size crack. Figure 3 The solder is coated in the form shown, the first solder 1 is filled into the gap 4, and the surface is scraped flat so that the surface of the first solder 1 is flush with the surface of the sample 3; after filling the first solder 1, a layer of second solder 2 is coated on its surface so that the first solder 1 is completely covered.
[0030] Next, the DD6 alloy samples were placed in a vacuum furnace for brazing, and the vacuum furnace was evacuated to a pressure of less than 4×10 -2 Pa, then began to heat up, heated to 1190℃ and kept warm for 2h, cooled to 80℃ and then taken out of the furnace to complete the brazing. Then the parts were kept warm at 1120℃ for 4h, cooled to 870℃ and kept warm for 32h for aging treatment.
[0031] Metallographic analysis of brazing samples, such as Figure 4 As shown, it can be seen that the structure of weld 5 is uniform and closely combined with the matrix of sample 3, without gaps, holes and unwelded defects. Standard samples were cut to test the tensile properties of the weld. The high-temperature tensile strength at 1000°C was about 433MPa, reaching 60% of the parent material performance.
[0032] In another embodiment, two sections of DD6 alloy samples are used to simulate the nickel-based single crystal high-temperature alloy parts to be repaired. The brazing alloy is prepared according to the following ratio: by weight, 15.3% Cr, 5.5% Co, 4.3% W, 1.3% Ta, 2.2% Al, 0.9% Mo, 2.9% B, 4.5% Hf, 2.1% Re, and the balance is Ni and unavoidable impurities. The brazing alloy and the base alloy are treated separately by vacuum gas atomization to prepare powders. Part of the brazing powder is evenly mixed with the base powder in a weight ratio of 1:3. The brazing powder is mixed with a binder to obtain a second brazing material in a paste state; the mixed powder of the brazing powder and the base powder is mixed with a binder to obtain a first brazing material in a paste state.
[0033] The surfaces of the two DD6 alloy samples were polished and cleaned with alcohol to remove the oil on the surface to determine the surface composite cleanliness requirements of the samples. The gap between the two DD6 alloy samples was controlled by a fixture to maintain a gap of about 0.3mm to simulate the state of a part with a large-size crack. Figure 3 The solder is coated in the form shown, the first solder 1 is filled into the gap 4, and the surface is scraped flat so that the surface of the first solder 1 is flush with the surface of the sample 3; after the first solder 1 is filled, a layer of the second solder 2 is coated on the surface so that the first solder 1 is completely covered. In a preferred embodiment, the coverage of the second solder 2 is slightly larger than the width of the gap 4, and the surface formed by the coating of the second solder 2 forms a naturally transitional arc.
[0034] Next, the DD6 alloy samples were placed in a vacuum furnace for brazing, and the vacuum furnace was evacuated to a pressure of less than 4×10 -2 Pa, then start heating, heating to 1220℃ and keeping it for 1h, cooling to 80℃ and then taking it out of the furnace to complete the brazing. Then keep the parts at 1120℃ for 4h, cool to 870℃ and keep it for 32h for aging treatment.
[0035] Metallographic analysis of brazing samples, such as Figure 5 As shown, it can be seen that the structure of weld 5 is uniform and closely combined with the matrix of sample 3, without gaps, holes and unwelded defects. Standard samples were cut to test the tensile properties of the weld. The high-temperature tensile strength at 1000°C was about 595MPa, reaching 80% of the parent material performance.
[0036] In another embodiment, two sections of DD6 alloy samples are used to simulate the nickel-based single crystal high-temperature alloy parts to be repaired. The brazing alloy is prepared according to the following ratio: by weight, 14.3% Cr, 10.5% Co, 1.2% W, 3.5% Ta, 2.5% Al, 3.8% Mo, 3.2% B, 2.9% Hf, 0.7% Re, and the balance is Ni and unavoidable impurities. The brazing alloy and the base alloy are treated separately by vacuum gas atomization to prepare powders. Part of the brazing powder is uniformly mixed with the base powder in a weight ratio of 2:3. The brazing powder is mixed with a binder to obtain a second brazing material in a paste state; the mixed powder of the brazing powder and the base powder is mixed with a binder to obtain a first brazing material in a paste state.
[0037] The surfaces of the two DD6 alloy samples were polished and cleaned with alcohol to remove the oil on the surface to determine the surface composite cleanliness requirements of the samples. The gap between the two DD6 alloy samples was controlled by a fixture to maintain a gap of about 0.3mm to simulate the state of a part with a large-size crack. Figure 3 The solder is coated in the form shown, the first solder 1 is filled into the gap 4, and the surface is scraped flat so that the surface of the first solder 1 is flush with the surface of the sample 3; after filling the first solder 1, a layer of second solder 2 is coated on its surface so that the first solder 1 is completely covered.
[0038] Next, the DD6 alloy samples were placed in a vacuum furnace for brazing, and the vacuum furnace was evacuated to a pressure of less than 4×10 -2 Pa, then began to heat up, heated to 1200℃ and kept warm for 1.5h, cooled to 80℃ and then taken out of the furnace to complete the brazing. Then the parts were kept warm at 1120℃ for 4h, cooled to 870℃ and kept warm for 32h for aging treatment.
[0039] Metallographic analysis of brazing samples, such as Figure 6As shown, it can be seen that the structure of weld 5 is uniform and closely combined with the matrix of sample 3, without gaps, holes and unwelded defects. Standard samples were cut to test the tensile properties of the weld. The high-temperature tensile strength at 1000°C was about 581MPa, reaching 80% of the parent material performance.
[0040] In some embodiments, the wedge-shaped cracks in the actual parts are brazed and repaired. The narrower parts of the wedge-shaped cracks, such as the areas with a width less than 0.25 mm, can be directly filled with brazing powder. For the areas with a width greater than 0.25 mm, the brazing repair material can be set in the manner provided in the above embodiments to achieve effective brazing repair of the wedge-shaped cracks. In other embodiments, the above brazing repair material and brazing repair method can also be applied to other grades of nickel-based single crystal high-temperature alloys such as DD4 alloy or CMSX-4 alloy. In different embodiments, the mixing ratio of brazing powder and base material powder in the first brazing material can be reasonably adjusted according to factors such as the gap width and the melting point of the base material. In some embodiments, when the gap width is narrow or the melting point of the base material is low, the proportion of brazing powder can be appropriately increased; when the gap width is wide or the melting point of the base material is high, the proportion of brazing powder can be appropriately reduced.
[0041] In a comparative example, a solder alloy is prepared as a powder with a weight ratio of 9.6% Cr, 10.7% Co, 1.5% W, 4.3% Ta, 3.7% Al, 2.5% B, and the balance Ni. The solder alloy powder is fully mixed with the DD6 alloy powder in a ratio of 1:2, and a binder is added to make it into a paste. Two sections of DD6 alloy samples are used to simulate the gap to be welded. The DD6 alloy samples are arranged at a spacing of 0.3 mm, and the gap is filled with paste solder and scraped flat. Then, a layer of paste solder is spread on the surface of the paste solder, so that the solder is arranged between the samples in the same total amount and distribution as in the embodiment. The sample is placed in a vacuum furnace and evacuated to a pressure below 4×10 -2 Pa, heated to 1220℃ for 1h, cooled to 80℃ and then taken out of the furnace. Then the welded sample was kept at 1120℃ for 4h, cooled to 870℃ for 32h for aging treatment. Metallographic analysis of the comparative sample was performed, as shown in Figure 7 As shown, it can be seen that there is a large range of unwelded defects 6 in the welding area between the samples 3.
[0042] The nickel-based single crystal high-temperature alloy brazing repair material provided in the embodiment of the present invention has a first brazing filler metal filled in the weld with less low-melting-point brazing powder, thereby reducing the large-sized block or continuous chain brittle intermetallic compounds that may be formed during the brazing process. At the same time, the second brazing filler metal with a lower melting point in the outer layer can fully form a liquid phase, effectively filling the gaps between the parent material powders and between the parent material powders and the part substrate, thereby effectively reducing defects such as holes and gaps in the weld area.
[0043] The brazing repair method for nickel-based single crystal high-temperature alloy provided in the above embodiment is used for vacuum brazing, and multiple parts can be brazed and repaired at the same time, which improves production efficiency and reduces the influence of the brazing structure on the structure and mechanical properties of the single crystal high-temperature alloy. In some embodiments, after brazing and two repair welding, the performance of the single crystal part after simulated thermal cycle can still reach more than 95% of the performance of the brazed single crystal part.
[0044] The purpose of the above embodiments is to further explain the present invention in detail in conjunction with the accompanying drawings so that those skilled in the art can understand the technical concept of the present invention. Within the scope of the claims of the present invention, the optimization or equivalent replacement of the components and method steps involved, and the combination of implementation methods in different embodiments without conflict of principle, all fall within the protection scope of the present invention.
Claims
1. A nickel-based single crystal high-temperature alloy brazing repair material, characterized in that: The method comprises a first brazing filler metal, wherein the first brazing filler metal comprises a uniformly mixed brazing powder and a base material powder having the same composition as the nickel-based single crystal high-temperature alloy to be repaired; The brazing powder comprises the following components by weight: 8%-18% Cr, 3%-12% Co, 1%-6% W, 1%-6% Ta, 2%-6% Al, 1%-5% B, no more than 4% Mo, no more than 5% Hf, no more than 3% Re, and the balance is Ni and unavoidable impurities; The weight ratio of the brazing powder in the first brazing material is 5% to 50%.
2. The nickel-based single crystal high-temperature alloy brazing repair material according to claim 1, characterized in that: The weight ratio of the brazing powder in the first brazing material is 10%-40%.
3. The nickel-based single crystal high-temperature alloy brazing repair material according to claim 1 or 2, characterized in that: The particle sizes of the brazing powder and the base material powder do not exceed 110 μm.
4. The nickel-based single crystal high-temperature alloy brazing repair material according to claim 1 or 2, characterized in that: The particles of the brazing powder and the base material powder are spherical or nearly spherical.
5. The nickel-based single crystal high-temperature alloy brazing repair material according to claim 1 or 2, characterized in that: It also includes a second solder, which is the solder powder and is used to be coated on the surface of the first solder.
6. The nickel-based single crystal high-temperature alloy brazing repair material according to claim 1 or 2, characterized in that: The nickel-based single crystal high temperature alloy is DD4, DD6 or CMSX-4 alloy.
7. A brazing repair method for nickel-based single crystal high-temperature alloy, characterized in that: The method adopts the nickel-based single crystal high-temperature alloy brazing repair material as claimed in any one of claims 1 to 6 as the brazing material, and comprises the following steps: Providing a part to be repaired having a crack, and filling the crack with the first solder; Coating the brazing powder on the surface of the first brazing material filled in the crack until the first brazing material is completely covered; The parts to be repaired are vacuum heated at a temperature of 1150° C.-1230° C. and a heat preservation time of 20 min-180 min to complete the brazing repair.
8. The brazing repair method for nickel-based single crystal high-temperature alloy according to claim 7, characterized in that: The maximum width of the crack of the part to be repaired is not less than 0.25 mm.
9. The brazing repair method for nickel-based single crystal high-temperature alloy according to claim 7, characterized in that: The first solder filled in the crack is flush with the surface of the part to be repaired.
10. The brazing repair method for nickel-based single crystal high-temperature alloy according to claim 7, 8 or 9, characterized in that: The parts repaired by brazing are subjected to high-temperature tensile testing at 1000°C, and the strength is not less than 60% of the parent material.
Citation Information
Patent Citations
NiCoCrWNbMoAlSiBTiC powder brazing material
CN101780610A
Method for manufacturing a part for a turbomachine
CN107107194A
Turbine guider crake brazing repair method
CN107234311A
Nickel-manganese-chromium-cobalt-boron alloy brazing filler metal powder and preparation method thereof
CN111975241A
Preparation method of nickel-based as-cast brazing powder
CN113996796A
Cited By
Crack repairing method for additive manufacturing nickel-based high-temperature alloy part
CN119952344A
A method of crack repair for an additively manufactured nickel-based superalloy component
CN119952344B
